2016
DOI: 10.1039/c6ra23717g
|View full text |Cite
|
Sign up to set email alerts
|

Orientation symmetry breaking in self-assembled Ce1−xGdxO2−ynanowires derived from chemical solutions

Abstract: A novel approach to perform an independent study of the nucleation and coarsening of Ce0.9Gd0.1O2−ynanowires is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 86 publications
(115 reference statements)
3
24
0
Order By: Relevance
“…CGO NDs grown on (001)YSZ substrates have a larger strain configuration than those grown on (001)LAO ( (001)CGO||(001)YSZ~ -5% vs (001)CGO||(001)LAO~ -1%) 48 . Large values of strain will contribute increasing the nucleation barrier for a given supersaturation as reported before 44,63 . Therefore, the energy required to overcome the nucleation barrier and for the stabilization of nuclei will be higher which means that higher temperatures are needed.…”
Section: Heating Ramp and Temperature Dependence Of Nucleationsupporting
confidence: 51%
See 4 more Smart Citations
“…CGO NDs grown on (001)YSZ substrates have a larger strain configuration than those grown on (001)LAO ( (001)CGO||(001)YSZ~ -5% vs (001)CGO||(001)LAO~ -1%) 48 . Large values of strain will contribute increasing the nucleation barrier for a given supersaturation as reported before 44,63 . Therefore, the energy required to overcome the nucleation barrier and for the stabilization of nuclei will be higher which means that higher temperatures are needed.…”
Section: Heating Ramp and Temperature Dependence Of Nucleationsupporting
confidence: 51%
“…It also seems to be the same case for closed CSD systems where atoms are already deposited on the substrate surface prior to the formation of nanostructures ( Figure S3). theoretical studies where we have demonstrated that coarsening of NWs along their length is thermodynamically driven by the continuous reduction of the system's energy 63 . Therefore, NWs' elongation seems to be a kinetically-driven thermodynamic process.…”
Section: Thermally-activated Coarsening Of Cgo Nanostructuresmentioning
confidence: 91%
See 3 more Smart Citations